2021
DOI: 10.17582/journal.jis/2021/7.1.152.160
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Improves Rice Seed Germination under Induced Drought Stress

Abstract: R ice is one of the most important food commodities and provides major portion of daily calories requirement, especially in underdeveloped and developing countries (Fukagawa and Ziska, 2019). The world population is increasing at an exponential rate, demanding approximately 70% increase in food production to meet the food security targets by 2050 (Fróna et al., 2014). Water scarcity or drought is one of the biggest threats to food security worldwide and could reduce crop production by 50% (Budak et al., 2015).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In this study, a significant mean square due to the main effects of irrigation conditions, cultivars, SA, as well as their interactions on grain yield and most studied traits was observed. The significant effects of cultivars, irrigation conditions, SA, and their interactions on rice quantitative traits were previously reported by [18,20,21,38,46,47]. The irrigation conditions, followed by cultivars and SA concentrations, determined a large proportion of the total variation in the grain yield and most studied traits.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…In this study, a significant mean square due to the main effects of irrigation conditions, cultivars, SA, as well as their interactions on grain yield and most studied traits was observed. The significant effects of cultivars, irrigation conditions, SA, and their interactions on rice quantitative traits were previously reported by [18,20,21,38,46,47]. The irrigation conditions, followed by cultivars and SA concentrations, determined a large proportion of the total variation in the grain yield and most studied traits.…”
Section: Discussionmentioning
confidence: 56%
“…The genetic variation between rice cultivars is fundamental to the development of drought tolerance cultivars because they react reversibly to drought stress [49]. Under higher osmotic stress levels, the variation of SA concentrations shows more pronounced effects [21]. These indicate that there was sufficient desirable variability in the two rice cultivars' responses to SA concentrations under normal and drought irrigation conditions, which may be utilized in improving the rice grain yield under drought regions in Egypt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in Hordeum marinum and H. vulgare, seed conditioning with SA significantly improved aerial and root growth under different salt treatments (up to 200 mM), suggesting that the effectiveness of this approach may vary with the species and the intensity of stress applied (YOUSSEF et al, 2023). And treatment with salicylic acid may be one of the suitable alternatives to reduce the deleterious effects of salt stress in rice, where joint application improved its vegetative characteristics and showed beneficial effects on seed germination and seedling vigor index (FARHANGJOO et al, 2020;RAFIQ et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it acts as a signaling molecule that induces plant tolerance to stress by regulating physiological processes and providing protection against biotic and abiotic stresses, such as those caused by excess salt in the substrate (SILVA et al, 2020). In this regard, several authors have reported that the exogenous application of salicylic acid increases plant tolerance to salt stress, as observed for example in rice (FARHANGJOO et al, 2020;RAFIQ et al, 2021), pepper (KUMAR et al, 2022), wheat (ABDI et al, 2023, sugarcane (APON et al, 2023), eggplant (MADY et al, 2023), and barley (YOUSSEF et al, 2023.…”
Section: Introductionmentioning
confidence: 99%